Origen y evolución de la comunidad palestina en Chile - Espín Ocampo, Julieta (2020)
The article analyzes the characteristics of the Palestinian community in Chile, resorting to both the origin and historical evolution and the process of identity construction, especially through the institutions that they have created in that country. Although this community is already integrated into Chilean society with the loss of identity elements such as the Arabic language, it maintains a sense of belonging and cohesion within its members, in addition to interest and political commitment regarding the land of their ancestors.